A study on the determinants of life insurance demand towards residences in Puchong Intan Apartment in Puchong, Selangor / Nur Fazlin Zainal and Nurul Fatihah Jamaludin - Zainal, Nur Fazlin; Jamaludin, Nurul Fatihah (Faculty of Business and Management, 2016)
This study is conducted as a partial fulfilment of the coursework of Industrial Training Project Paper. The title of this study is The Determinants of Life Insurance Demand Towards Residences in Puchong Intan Apartment in Puchong, Selangor. In order to achieve the stated primary purpose in the research, there are several objectives, which are needed to be taken into consideration in carrying out this study. All these objectives are to identify level of knowledge, promotion and price towards individual demand in life insurance, to identify the relationship between knowledge and individual demand of life insurance, to identify the relationship between promotion and individual demand of life insurance, to identify the relationship between price and individual demand of life insurance, and to determine which factor is the most significant to influence the individual demand of life insurance. This study was conducted in Puchong Intan Apartment in Puchong Intan, Selangor. Through this study, it will provide insurance company the information needed in order to increase the individual demand of life insurance